Clinical Evidence of Probiotics for Acne - Ike Martyani; Nelva K. Jusuf (Indonesian Journal of Global Health Research, 2026)
Acne vulgaris is a common inflammatory skin disorder influenced by microbial imbalance, immune dysregulation, and excessive sebum production. Recently, probiotics have gained attention as a potential adjunct therapy due to their ability to regulate inflammation, improve skin barrier function, and modulate the gut–skin axis. This study aimed to evaluate the existing clinical evidence on the effectiveness of probiotics as a therapeutic approach for acne vulgaris. A systematic literature review was conducted following PRISMA 2020 guidelines. Electronic searches were performed in PubMed, Scopus, Web of Science, and Google Scholar using the keywords “probiotics”, “acne vulgaris”, “microbiome”, “oral probiotics”, “topical probiotics”, and “clinical trial” for studies published between 2000 and 2024. A total of 319 records were identified. After screening and eligibility assessment, 4 clinical trials met the inclusion criteria. Data were extracted and synthesized using a narrative approach due to heterogeneity of probiotic strains, dosages, and outcome measures. Four clinical trials met the inclusion criteria, consisting of three oral probiotic studies and one topical formulation study. The results demonstrated that probiotics significantly reduced acne severity, lesion counts, and inflammation. Oral probiotics, such as Lactobacillus plantarum, Lacticaseibacillus rhamnosus, and probiotic combinations with Arthrospira platensis improved skin hydration, modified sebum composition, and positively influenced skin microbiota. A topical Lactobacillus paracasei formulation showed comparable effectiveness to benzoyl peroxide in reducing inflammatory lesions, with fewer adverse effects. All probiotic treatments were well tolerated and associated with minimal side effects. Current evidence indicates that both oral and topical probiotics may serve as effective adjunct therapies for acne vulgaris by reducing inflammation, regulating the skin microbiome, and enhancing skin barrier function. However, variability in strains, treatment regimens, and study designs limits standardization. Larger, well-designed, strain-specific randomized trials are needed to determine optimal probiotic therapy for acne management.